Advanced Theragenerative Biomaterials with Therapeutic and Regeneration Multifunctionality. (29th June 2020) - Chen, Baoding; Xiang, Huijing; Pan, Shanshan; Yu, Luodan; Xu, Tianming; Chen, Yu
Abstract: All tissues and organs can be affected by diseases, and treatments for these diseases can cause damage to surrounding healthy tissues and organs. Therefore, treatment is required that involves disease therapy alongside tissue/organ regeneration. The design, construction, and biomedical applications of biomaterial platforms with both disease‐therapeutic and tissue‐regeneration multifunctionalities are in demand, which are herein referred to as theragenerative (abbreviation of therapy and regeneration) biomaterials. Due to the rapid development of theragenerative biomaterials in versatile biomedical applications, this progress report aims to summarize, discuss, and highlight the rational construction of distinctive theragenerative biomaterials with intrinsic therapeutic performance and tissue‐regeneration bioactivity. Based on the intrinsic response to either external physical triggers (e.g., photonic response or magnetic‐field response) or endogenous disease microenvironments (e.g., mild acidity or overexpressed hydrogen peroxide) and tissue‐regeneration bioactivity, these theragenerative biomaterials are extensively explored in various biomedical fields, including bone‐tumor therapy/regeneration, bone antibacterial therapy/regeneration, skin‐tumor therapy/regeneration, skin antibacterial therapy/regeneration, breast‐tumor therapy/adipose‐tissue regeneration, and osteoarticular‐tuberculosis therapy/bone‐tissue regeneration. The challenges faced and future developments of these distinctive theragenerative biomaterials are discussed, as are methods for further promoting their clinical translation. Abstract : Based on the specific response to either external physical triggers or endogenous disease microenvironments, as well as tissue regeneration properties, this progress report summarizes and discusses the rational construction of theragenerative biomaterials for both therapeutic applications and tissue regeneration. The challenges faced and future developments of these emerging theragenerative biomaterials are also discussed for promoting their further clinical translation.